TRANSFERSOME GEL FORMULATION OF AN ETHANOL EXTRACT OF APPLES (MALUS DOMESTICA MILL) CONTAINING ANTIOXIDANTS AND IN VITRO PENETRATION TESTING USING FRANZ DIFFUSION CELLS - Zesiorani, Nurarita Fadila; Anwar, Effionora (International Journal of Applied Pharmaceutics, 2017)
Objective: This study aims to formulate and characterize a transfersome apple peel extract, formulate it into a gel, and compare it with a control gel made without transfersome. Methods: Both gels were evaluated, stability tested, and penetration tested using Franz diffusion cells on the skin of female Sprague-Dawley rats. The transfersome preparations were formulated with different concentrations of the active substance, quercetin: 0.5% (F1); 0.7% (F2), and 1.0% (F3). Results: Based on the characterization results, F1 was selected as the optimum gel formulation because it had spherical morphology, a Dmean volume of 106.44±2.70 nm, a polydispersity index of 0.078±0.01, a zeta potential of −49.96±2.05 mV, and a drug efficiency entrapment percentage of 78.78±0.46%. The cumulative amount of quercetin that was penetrated with the transfersome gel was 1514.41±26.31 μg/cm2, whereas the penetration with the control gel extract was 1133.62±18.96 μg/cm2. The cumulative percentages of the penetrated gel transfersome and gel extract were 78.40±1.89% and 49.89±0.88%, respectively. The fluxes of transfersome gel and control gel extract were 52.33±0.11 μg/cm²/hrs and 40.89±0.68 μg/cm²/hrs, respectively. Conclusions: Based on these results, it can be concluded that the gel with transfersome exhibited better penetration than the gel extract alone.